Neutralization of Industrial Water by Electrodialysis - Oleksandr Petrov; Natalia Iwaszczuk; Tina Kharebava; Irina Bejanidze; Volodymyr Pohrebennyk; Nunu Nakashidze; Anton Petrov (Membranes, 2021)
The process of non-reagent adjustment of the pH of a NaCl solution (0.5 g/L) of different acidity was investigated by the method of bipolar electrodialysis on a device operating according to the K-system (concentration). The experiments were carried out in the range pH = 2.0–12.0 with monopolar cation-exchange MK-40 (for alkaline solutions) or anion-exchange MA-40 (for acidic solutions) and bipolar MB-2 membranes. The regularities of the change in the pH of the solution on the current density, process productivity and energy consumption for the neutralization process have been investigated. Revealed: with different productivity of the apparatus (Q = 0.5–1.5 m3/h), in the range of pH 3.0–11.0, with an increase in the current density, a neutral pH value is achieved. It has been shown that at pH above 11.0 and below 3.0, even at high current densities (i > 20 A/m2), its value cannot be changed. This is due to the neutralization of the H+ or OH− ions generated by the bipolar membrane by water ions, which are formed as a result of the dissociation of water molecules at the border of the monopolar membrane and the solution under conditions when the value of current exceeds the limiting value.